Critiquing the heteronormativity of the banal citizen in New Zealand's mediated civil union debate - Goodwin, Ian; Lyons, Antonia C.; Stephens, Christine (Gender, place and culture : a journal of feminist geography, 2014)
This article extends Billig's (1995) landmark thesis on banal nationalism by considering how processes of national deixis circumscribe the boundaries of citizenship and forms of belonging within nation-states. Drawing on critical analyses of sexual citizenship, the article provides a discursive analysis of the debate over civil union in the New Zealand mainstream press during 2004-2005. It argues that this mediated debate represented an historical moment where the routine deictic flagging of the nation, and the correlated flagging of the 'banal citizen', fundamentally broke down, thereby allowing this unmarked and 'ordinary' process to be systematically examined. Four major discourses are identified in press coverage: 'Homosexual' subjects as abnormal and disordered, tolerance, equality and human rights, the sanctity of marriage and the preservation of the family (and the social order). Although the passing of the Civil Union Act does mark a (faltering) step forward in sexual equality, we argue that the presence of these discourses suggests that forms of both ontological and cultural heterosexism persist in New Zealand society. Despite the Act conferring new legal rights, ultimately we conclude that the four discourses act to restrict the extent to which 'homosexual' subjects are considered 'valid' and 'legitimate' citizens. In continuing to structure the public politics of sexual citizenship in New Zealand, these discourses have influenced recent debates over legislative moves towards 'marriage equality' in ways that raise concerns over the continuation of heterosexist norms, as well as exclusionary forms of homo-nationalism. More generally, this research demonstrates the effectiveness of Billig's work as a valuable and productive analytic lens to explicate concerns over the exclusionary nature of citizenship itself.